Bagging and non‐bagging treatment on the dissipation and residue of four mixed application pesticides on banana fruit. (20th December 2020) - Wang, Ye; Song, Qingmei; Wang, Fei; Tang, Shouying; Pan, Tingtiao; Zhang, Yuping; Hu, Deyu
Abstract: BACKGROUND: Bananas are vulnerable to disease and insect pests after producing fruit. In order to increase the yield and produce high‐quality fruit, the insecticides and fungicides are mixed and applied 2–3 times on banana, then the fruit is bagged. Buprofezin, imidacloprid, difenoconazole, and pyraclostrobin are widely used on banana. However, there is a lack of research on the effect of fruit bagging on pesticide dissipation and residues on bananas. RESULTS: A versatile liquid chromatography–tandem mass spectrometry method with modified QuEChERS sample preparation has been developed for the determination of buprofezin, imidacloprid, difenoconazole, and pyraclostrobin in bananas. The recovery of four pesticides was satisfactory (74.96–98.63%) with reasonable relative standard deviation (≤ 8.78%). In Hainan and Guangzhou, the half‐lives of the four pesticides were 4.68–13.9 and 5.63–20.4 days in non‐bagged and bagged bananas, respectively. The significance analysis of the half‐lives in the two sites showed that the dissipation rates of the three pesticides (imidacloprid, difenoconazole, pyraclostrobin) on whole bananas were significantly decreased by the effect of bagging ( P < 0.05). However, there was no significant difference in the degradation of half‐life of buprofezin under bagging and without bagging ( P > 0.05). CONCLUSION: The high vapor pressure and the non‐systemic property cause buprofezin to evaporate and dissipate the fastest among the four studied pesticides. The ultimate residues of four pesticides in bananas are lower than the maximum residue limits in China after three times of mixed applications under bagging or non‐bagging. The results provide scientific data for evaluating the safety of four pesticides in banana bagging. © 2020 Society of Chemical Industry